2019
DOI: 10.1111/gcb.14627
|View full text |Cite
|
Sign up to set email alerts
|

Satellite detection of cumulative and lagged effects of drought on autumn leaf senescence over the Northern Hemisphere

Abstract: Climate change has substantial influences on autumn leaf senescence, that is, the end of the growing season (EOS). Relative to the impacts of temperature and precipitation on EOS, the influence of drought is not well understood, especially considering that there are apparent cumulative and lagged effects of drought on plant growth. Here, we investigated the cumulative and lagged effects of drought (in terms of the Standardized Precipitation-Evapotranspiration Index, SPEI) on EOS derived from the normalized dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(79 citation statements)
references
References 87 publications
2
75
1
1
Order By: Relevance
“…Some studies have indicated that LOS has been prolonged in recent years, a change that is more closely associated with temperature than with precipitation, and that the different patterns between the phenological metrics and climate factors may be associated with their growth environment [74]. Several studies have also proposed that a time-lagged and cumulative effect exists between vegetation growth and climate changes [32,[75][76][77]. Different lagged and cumulated effects between the phenological metrics and climate factors have been noticed and attributed to species, and locations, at diverse temporal and spatial scales [22].…”
Section: Relationships Between Phenology Metrics and Climatic Factorsmentioning
confidence: 99%
“…Some studies have indicated that LOS has been prolonged in recent years, a change that is more closely associated with temperature than with precipitation, and that the different patterns between the phenological metrics and climate factors may be associated with their growth environment [74]. Several studies have also proposed that a time-lagged and cumulative effect exists between vegetation growth and climate changes [32,[75][76][77]. Different lagged and cumulated effects between the phenological metrics and climate factors have been noticed and attributed to species, and locations, at diverse temporal and spatial scales [22].…”
Section: Relationships Between Phenology Metrics and Climatic Factorsmentioning
confidence: 99%
“…We acquired monthly SPEI for 1982 to 2015 at a spatial resolution of 0.5°, calculated using the difference between precipitation and potential ET from the SPEI base v. 2.5 at Consejo Superior de Investigaciones Científicas (56). The SPEI data set consisted of multiscalar monthly SPEI, so we selected 3-mo SPEI, given this time duration representing the accumulated climatic water balance with the highest correlation with DFS as the final water indicator (22). X-band (10.7 GHz) VOD was obtained from the land parameter data record (LPDR version 2) developed by the Numerical Terradynamic Simulation Group at the University of Montana (57).…”
Section: Methodsmentioning
confidence: 99%
“…Global increases in autumn temperature could delay DFS (14,20), yet there are also studies showing either earlier or relatively stable DFS, with a possible explanation from opposite changes in DFS in response to daytime and nighttime warming (21). Decreases in precipitation and associated drought may have more complicated influences on DFS, depending on the severity of drought and on regional characteristics of plant functional types (22). In addition to changes in temperature and precipitation, wind speed over the last three decades shows widespread decreasing trends in the northern hemisphere (23,24) with possible impacts on plant growth, chemical composition, structure, and morphology (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…The Normalized Difference Vegetation Index (NDVI), which is derived from satellite remote sensing, has been widely applied in the estimation of land surface phenology in recent years [15]- [17]. Various methods have been developed to extract the EOS from the NDVI [18], which generally involve two main steps: elimination of the noise in NDVI data and identification of the EOS [19], [20]. In the first step, several methods, such as the Savitzky-Golay filter [21], Fourier decomposition [22], and logistic function [23], have been adopted to eliminate the noise in NDVI data, which is due to contamination by cloud cover, seasonal snow, and atmospheric variability.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have attempted to explain the changes in EOS through daily mean temperature and precipitation [20], [28]. However, the temperature has experienced faster warming during the nighttime than daytime over the past five decades [29], which has an asymmetric effect on phenological parameters [30].…”
Section: Introductionmentioning
confidence: 99%